Mechanical and tribological properties of Zr-based bulk metallic glass for sports applications. (15th February 2016) - Khun, N.W.; Yu, H.; Chong, Z.Z.; Tian, P.; Tian, Y.; Tor, S.B.; Liu, E.
Abstract: The microstructure, and mechanical and tribological properties of zirconium-based bulk metallic glass (Zr-BMG) were investigated for golf club heads. The Zr-BMG had a fully amorphous structure without any detectable crystalline phases. The hardness and Young's modulus of the Zr-BMG were relatively high even though they were lowered by about 36% and 28% respectively by the increased indentation depth from 200 to 1000 nm due to strain softening during the nanoindentation test. The tribological behaviour of the Zr-BMG was investigated by sliding against alumina (Al2 O3 ), 100Cr6 steel or polymethyl-methacrylate (PMMA) balls under normal loads of 1–3 N. The wear of the Zr-BMG tested against the Al2 O3 and 100Cr6 balls became higher with higher normal loads while a higher wear resistance of the Al2 O3 ball than that of the 100Cr6 ball caused a higher wear of the Zr-BMG. A much lower wear resistance of the PMMA ball than that of the Zr-BMG resulted in a preferential wear of the PMMA ball without generating any apparent wear of the Zr-BMG during the testing. The Zr-BMG tested against the Al2 O3 ball exhibited the highest wear under all the normal loads due to the highest wear resistance of the Al2 O3 ball among the counter balls. Graphical abstract: Highlights: Commercial Zr-based bulk metallic glass investigated for golf club heads has relatively high hardness and Young's modulus. More severe wear is observed against Al2 O3 counter ball than against 100Cr6 steel counter ball. Zr-based bulk metallic glass does not exhibit any apparent wear against PMMA counter ball. Wear of Zr-based bulk metallic glass induced by Al2 O3 ball shows fatigue wear characteristics.